The Road to Found Poetry : Understanding People's Perceptions and Lived Experiences Creatively - Alsawayfa, Fadel (Arts, Creativities, and Learning Environments in Global Perspectives, 2025)
The Road to Found Poetry: Understanding People's Perceptions and Lived Experiences Creatively is a book based on the author's Educational Doctorate thesis. The book introduces the use of found poetry as an alternative means of knowing and understanding in various educational and non-educational contexts. Its ambition is to encourage educational researchers, educators, academics, undergraduate and postgraduate students, and practitioners interested in experimenting with a novel approach of analysis, presentation and dissemination that helps in gaining a deeper insight of research participants' experiences. The Road to Found Poetry moves beyond the traditionally accepted methods of doing research and offers a better understanding of people's perceptions and lived experiences. This new arts-based research methodology is participatory in nature and gives voice to researchers and research participants. It creates possibilities for researcher's reflexivity and participant's agency.